Roles and mechanisms of NSUN2-mediated RNA m5C modification in cancer progression and immune modulation - Li, Chunhong; Yuan, Yixiao; Jiang, Xiulin; Wang, Qiang (Frontiers in Immunology, 2025)
RNA epigenetic modifications critically regulate gene expression, with 5-methylcytosine (m5C) emerging as an important mark in cancer biology. NSUN2, a key m5C methyltransferase, modifies diverse RNA species, thereby influencing RNA stability, processing, export, and translation. Accumulating evidence indicates that NSUN2 promotes tumorigenesis by enhancing cell proliferation, supporting drug resistance, driving epithelial–mesenchymal transition, and reprogramming metabolic pathways. Clinically, its dysregulated expression is associated with poor prognosis and potential as a biomarker or therapeutic target. Beyond intrinsic tumor functions, NSUN2 also shapes the tumor immune microenvironment by regulating immune checkpoint molecules, cytokine networks, and immune cell activities, ultimately contributing to immune evasion and influencing immunotherapy efficacy. This review summarizes current insights into the roles and mechanisms of NSUN2 in cancer progression and immune modulation, and discusses challenges and future opportunities for therapeutic exploration.